Estimation of Vibration Characteristics of a Space Manipulator From Air Bearing Supported Test Data - Li, Haiquan; Wei, Qingqing; Liang, Jianxun; Ren, Weiyan; Tang, Zixin; Li, Delun (Frontiers in Robotics and AI, 2021)
Space manipulators have attracted much attention due to their implications in on-orbit servicing in recent years. Air-bearing based support equipment is widely used for ground test to offset the effect of gravity. However, air-bearing support introduce a new problem caused by additional inertial and mass properties. Additional mass and inertial load will influence the dynamics behavior, especially stiffness information and vibration response of the whole ground test system. In this paper, a set of procedures are presented to remove the influence of air-bearings and identify the true equivalent joint stiffness and damping from the test data of a motor-braked space manipulator with air-bearing support. Inertia parameters are identified firstly. And then the equivalent joint stiffness and damping are determined by using a Genetic Algorithm (GA) method. Finally, true vibration characteristics of the manipulator are estimated by removing the additional inertia caused by the air-bearings. Moreover, simulations and experiments are carried out to validate the presented procedures.